Mitogenic effects of phosphatidylcholine nanoparticles on MCF-7 breast cancer cells - Gándola, Yamila Belén (2014)
Lecithins, mainly composed of the phospholipids phosphatidylcholines (PC), have many different uses in the pharmaceutical and clinical field. PC are involved in structural and biological functions as membrane trafficking processes and cellular signaling. Considering the increasing applications of lecithin-based nanosystems for the delivery of therapeutic agents, the aim of the present work was to determine the effects of phosphatidylcholine nanoparticles over breast cancer cellular proliferation and signaling. PC dispersions at 0.01 and 0.1% (w/v) prepared in buffer pH 7.0 and 5.0 were studied in the MCF-7 breast cancer cell line. Neutral 0.1% PC-derived nanoparticles induced the activation of the MEK-ERK1/2 pathway, increased cell viability and induced a 1.2 fold raise in proliferation. These biological effects correlated with the increase of epidermal growth factor receptor (EGFR) content and its altered cellular localization. Results suggest that nanoparticles derived from PC dispersion prepared in buffer pH 7.0 may induce physicochemical changes in the plasma membrane of cancer cells which may affect EGFR cellular localization and/or activity, increasing activation of the MEK-ERK1/2 pathway and inducing proliferation. Results from the present study suggest that possible biological effects of delivery systems based on lecithin nanoparticles should be taken into account in pharmaceutical formulation design.